Earth tectonics as seen by GOCE - Enhanced satellite gravity gradient imaging. Issue 1 (December 2018) - Ebbing, Jörg; Haas, Peter; Ferraccioli, Fausto; Pappa, Folker; Szwillus, Wolfgang; Bouman, Johannes
Abstract Curvature components derived from satellite gravity gradients provide new global views of Earth's structure. The satellite gravity gradients are based on the GOCE satellite mission and we illustrate by curvature images how the Earth is seen differently compared to seismic imaging. Tectonic domains with similar seismic characteristic can exhibit distinct differences in satellite gravity gradients maps, which points to differences in the lithospheric build-up. This is particularly apparent for the cratonic regions of the Earth. The comparisons demonstrate that the combination of seismological, and satellite gravity gradient imaging has significant potential to enhance our knowledge of Earth's structure. In remote frontiers like the Antarctic continent, where even basic knowledge of lithospheric scale features remains incomplete, the curvature images help unveil the heterogeneity in lithospheric structure, e.g. between the composite East Antarctic Craton and the West Antarctic Rift System.